Balance and gait in the elderly: A contemporary review. Issue 1 (4th February 2019) - Osoba, Muyinat Y.; Rao, Ashwini K.; Agrawal, Sunil K.; Lalwani, Anil K.
Abstract : Background: The prevalence of balance and gait deficits increases with age and is associated with the increased incidence of falls seen in the elderly population; these falls are associated with significant morbidity and mortality. Objectives: To review changes in gait and balance associated with aging and the effect of visual perturbations on gait and balance in the elderly to provide a basis for future research. Methods: PubMed and Cochrane Library were searched for articles from 1980 to present pertaining to gait and balance in older adults (>60) and younger adults (<60). Search terms included balance, posture, gait, locomotion, gait variability, gait disorders, gait disturbance, elderly, aging, falls, vision, visual, vestibular, and virtual reality. The references section of queried articles was also used to find relevant studies. Studies were excluded if subjects had a diagnosed gait or balance disorder. Results: Elderly adults show age‐related decline in sensory systems and reduced ability to adapt to changes in their environment to maintain balance. Elderly adults are particularly dependent on vision to maintain postural stability. Distinct changes in spatiotemporal gait parameters are associated with aging, such as slower gait and increased gait variability, which are amplified with exposure to visual perturbations. Increased gait variability, specifically with mediolateral perturbations, poses a particular challenge for elderly adults and is linked to increased falls risk. Virtual reality training has shown promising effects on balance and gait. Conclusion: Elderly adults show age‐related decline in balance and gait with increased gait variability and an associated increased risk of falls. Level of Evidence: 5